The sl(2) affine Toda model coupled to the matter: solitons and confinement - Blas, H. (World Scientific Publ Co Pte Ltd, 2001)
The so-called conformal affine Toda theory coupled to the matter fields (CATM), associated to the (s) over capl(2) affine Lie algebra, is studied. The conformal symmetry is fixed by setting a connection to zero, then one defines an off-critical model, the affine Toda model coupled to the matter (ATM). Using the dressing transformation method we construct the explicit forms of the two-soliton classical solutions, and show that a physical bound soliton-antisoliton pair (breather) does not exist. Moreover, we verify that these solutions share some features of the sine-Gordon (massive Thirring) solitons, and satisfy the classical equivalence of topological and Noether currents in the ATM model. We show, using bosonization techniques that the ATM theory decouples into a sine-Gordon model and a free scalar. Imposing the Noether and topological currents equivalence as a constraint, one can show that the ATM model leads to a bag model like mechanism for the confinement of the color charge inside the sine-Gordon solitons (baryons).